Mechanisms and approaches towards enhanced drought tolerance in cassava (Manihot esculenta) - Muiruri, K.S.; Ntui, V.O.; Tripathi, L.; Tripathi, J. (Elsevier, 2021)
Cassava (Manihot esculenta Crantz) is cultivated in tropical and subtropical regions for its edible tuberous roots and minimally for its leaves. It provides food and revenue to over eight hundred million people particularly in Africa. Generally, cassava is drought-tolerant, and sheds leaves in drought conditions resulting in significantly lower yields. Cassava drought management strategies need to focus on maximizing the utilization of molecular tools for crop establishment and yield. Developing strategies to produce cassava cultivars with drought tolerance is vital to extending crop yield under limited rainfall. In this review, recent progress applying molecular genetics, genomics, genetic engineering, and genome editing are reviewed.